Study On Reclycing Of Industrial Steel Waste In The Production Of Porcelain Tiles - Azman, Afif Hafizhan (Universiti Sains Malaysia, 2022)
Industrial steel waste also known as steel slag is a by-product from the steel making industry. The dumping of steel slag in the landfill are affecting the flora and fauna and can causes for land pollution around the area. So, recycling of the steel waste into another product is one of the best methods to reduce the steel waste in the landfill. In this research work, the Electric Arc Furnace and Ladle Furnace slag was used. The objective of this experiment is to fabricate porcelain tiles with various composition of steel slag (LF and EAF slag) at firing temperature 1200°C and 1210°C. This study also to evaluate the effect of different composition of steel slags at different firing temperature 1200°C and 1210°C to physical and mechanical properties of porcelain tiles. In this study, nine compositions are set, and one of them is set as a control. The composition of the steel slag used in this research work is 40wt%, 30wt%, 20wt%, 10wt%. Firstly, the raw materials (clay, feldspar, silica, steel slag) were mixed and milled, followed by drying. Next, the dried mixture was pressed for a rectangular shape (103 mm X 39 mm X 3.6 mm) at pressure 37 MPa and then the tiles were fired at temperatures 1200°C and 1210°C. The fired tiles were characterized by appearance observation, linear shrinkage, water absorption, apparent porosity, bulk density, modulus of rupture (MOR), X-Ray Diffraction (XRD), and scanning electron microscope (SEM) for morphology observation. Result obtained from this research work show that the tiles with composition 20wt% LF slag and 20wt% feldspar at firing temperature 1210°C has lowest water absorption (0.01%), apparent porosity (0.03%), highest bulk density (2.6g/cm3) and has highest value of MOR (33.68 MPa).